(3Yde GdGbJUGO h GdJMdjd GdGbJUGOjs - (3HSGe(B, (3GdMLGQs ((3HjQhJ(B:s (3OGQ Gdefgd GddHfGfj(B,s, 2010)
(3CgOGa h NUGFU GdYdGbGJ GdGbJUGOjI YfO GdcdGSjc , GdfXQjI GdcfRjI , GdGSYGQ h GdJhGRf GdGbJUGOj , GdefaYI h GbJUGO GdeDSSI , eaGgje h WQb bjGS GdONd (B( (3GdfGJL (B) (3GdeMdj , GdGSJKeGQ , GdSjGSI GdfbOjI h GdSjGSI GdeGdjI , GdJVNe , GdGShGb GdeGdjI , GdHWGdI , Gdfeh h GdJbdHGJ GdGbJUGOjI h ejRGf GdeOahYGJ GdOhdjI (B.s
(3eQGLY U(B.277 (3; eUWdMGJ U(B.269s
Keywords: (3GdGbJUGOs; (3GdJMdjd GdGbJUGOjs; (3Yde GdEbJUGOs